OWNERSHIP, PROPERTY, AND SUSTAINABILITY (Utah Environmental Law Review; Vol 31 No 1 (2011))
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Cambria","serif"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} For some three centuries, ever since the first European settlement of North America, the land has been seen as a vast and incomparably rich treasure waiting to be put to use. Indeed, the notion that it was underutilized by the indigenous people served as a central justification for the settlers to displace them. Transformation was seen not only as an opportunity but also as a kind of mission. To the settlers the wilderness was a challenge and an obstacle, wild in the sense that it was to be tamed rather than embraced for what it was. And it is a fair description of events to say that transformation is what happened unceasingly from the late seventeenth century until the latter part of the nineteenth century and the beginning of the twentieth century when the first refuges and parks were set aside in what we now think of as the early stirrings of a conservation movement. All this history is very familiar.